The Importance of Including Soil Properties When Disentangling the Drivers of Species Richness: The Case of the Alpine Genus Saxifraga L. in China - Liu, Lian; Xu, Ying; Tang, Yigong; Du, Weihua; Shao, Chen; Wu, Jianyong; Zhao, Lina; Zhang, Lei; Liu, Jianquan; Xu, Xiaoting (Frontiers in Ecology and Evolution, 2020)
Despite the numerous studies on the large-scale patterns of species richness, the spatial variation and determinants of species richness for alpine plant are still an outstanding question and critical to future biodiversity conservation. The genus Saxifraga is a typical alpine plant group with high species richness in the Himalaya-Hengduan mountain regions, China. We performed simple regression models and variance partitioning to assess the importance of different factors, especially soil-related ones, in driving Saxifraga richness patterns. The results showed that environmental energy, habitat heterogeneity, and soil heterogeneity together dominated the spatial variation of species richness. The coarse fragments volume of soil, elevation range, and soil heterogeneity, are positively related to Saxifraga richness. Soil slightly outperforms habitat heterogeneity in predicting the spatial variation of Saxifraga species richness with an explanatory power of 39.3% and 36.6%, respectively. Environmental energy, such as the maximum temperature of the warmest quarter, is negatively correlated with species richness and explains 44.8% of spatial variation of Saxifraga richness. Multiple regression models, including three variables, each representing energy, soil, and habitat heterogeneity, can only explain 53.1% variation of species richness. Variance partitioning outscored 26% of the shared effects of the three variables, while the independent effect of each variable is less than 10%. These results indicated the energy, soil, and habitat heterogeneity together are primary determinants of the spatial variation of Saxifraga species richness. However, there are probably other hidden factors predicting species richness variation due to the low explanatory power of the multiple regression models. Our study emphasizes the significance of soil properties in determining species richness patterns in China, especially for the alpine plant groups. The negative association of species richness with temperature suggests a potential threat of alpine biodiversity loss in HHM from future warming.